Challenges and perspectives in MS-based omics approaches for ecotoxicology studies: An insight on Gammarids sentinel amphipods - Calabrese, Valentina; Salvador, Arnaud; Clément, Yohann; Brunet, Thomas Alexandre; Espeyte, Anabelle; Chaumot, Arnaud; Geffard, Olivier; Degli-Esposti, Davide; Ayciriex, Sophie (Frontiers in Analytical Science, 2023)
The aquatic environment is one of the most complex biosystems, as organism at all trophic levels may be exposed to a multitude of pollutants. As major goals, ecotoxicology typically investigates the impact of toxic pollutants on the ecosystems through the study of sentinel organisms. Over the past decades, Mass Spectrometry (MS)-based omics approaches have been extended to sentinel species both in laboratory and field exposure conditions. Single-omics approaches enable the discovery of biomarkers mirroring the health status of an organism. By covering a restricted set of the molecular cascade, they turn out to only partially satisfy the understanding of complex ecotoxicological effects. In contrast, a more complete understanding of the ecotoxicity pathways can be accessed through multi-omics approaches. In this perspective, we provide a state-of-the-art and a critical evaluation on further developments in MS-based single and multi -omics studies in aquatic ecotoxicology. As case example, literature regarding gammarids freshwater amphipods, non-model sentinel organisms sensitive to pollutants and environmental changes and crucial species for downstream ecosystems, will be reviewed.